Malignant transformation in oral epithelial dysplasticlesions: An observational study - Anuhya Jayanthi; Sagar Krishna; Sunitha Carnelio; Vasudeva Guddattu; Spoorti Kulkarni (Journal of Health Sciences)
Introduction: This research study is a comprehensive analysis of cases oral epithelial dysplasia (OED) to oral squamous cell carcinoma (OSCC) over the past decade, with a particular focus on eliciting the frequency of malignant transformation (MT) of OED within this group of 328 patients in a tertiary center of Karnataka. Aim of this study is to investigate the likely correlation between OSCC and OED with demographic details, clinical parameters, and risk factors, highlighting the frequency of MT of OED to OSCC.